Aplikasi Sistem Pakar Sebagai Alat Screening Diagnosa Penyakit Diabetes Mellitus Menggunakan Metode Teorema Bayes Berbasis Android - Revika Yona; Noveri Lysbetty Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Health is the most important part of human life. Once function of human’s organs is disrupted, it might cause many diseases to be suffered. Diabetes Mellitus is a disease caused by increasing blood sugar levels (glucose) in human body. Moreover, Diabetes Mellitus is well identified as one of that causes deatht of people in the world. To reduce mortality, an appropriate preventive action is needed. Furthermore this research is intended to help the society in diagnosing early Diabetes Mellitus. This Expert System application is implemented on the Android platform. The method used is the Bayes Theorem and expert knowledge from internal medicine specialists. The diagnosis process of this Expert System is by selecting the symptoms experienced. As a result, the system calculate the possible value of the symptoms and displays the percentage of the Diabetes types as well as a solution or prevention that can be done. The acccuracy of the application is obtained of 100%.Keywords : Android, Bayes Theorem, Diabetes Mellitus, Expert System.